Sumoylated HSP90 is a dominantly inherited plasma cell dyscrasias risk factor - Preuss, Klaus-Dieter; Pfreundschuh, Michael; Fadle, Natalie; Regitz, Evi; Kubuschok, Boris (The Journal of clinical investigation, 2015)
Posttranslationally modified proteins serve as autoimmunogenic targets in a wide spectrum of autoimmune diseases. Here, we identified a posttranslationally modified paraprotein target (paratargs) in monoclonal gammopathies of undetermined significance (MGUS), multiple myelomas (MM), and Waldenstrom's macroglobulinemias (WM) using protein macroarrays that were sumoylated and screened for reactivity with paraproteins from MGUS, MM, and WM patients. We found that paraproteins from a proportion of European, African-American, and Japanese patients specifically reacted with the sumoylated heat-shock protein 90 β isoform-α (HSP90-SUMO1, where SUMO indicates small ubiquitin-like modifier), while no reactivity with HSP90-SUMO1 was detected in over 800 controls. HSP90-SUMO1 was present in blood cells from all patients with HSP90-SUMO1-binding paraproteins. We determined that the HSP90-SUMO1 carrier state is autosomal-dominantly inherited and caused by the inability of SUMO peptidase sentrin/SUMO-specific protease 2 (SENP2) to desumoylate HSP90-SUMO1. HSP90-SUMO1 was detected in a small percentage of healthy individuals from all backgrounds; however, only MGUS, MM, and WM patients who were HSP90-SUMO1 carriers produced HSP90-SUMO1-specific paraproteins, suggesting that sumoylated HSP90 promotes pathogenesis of these diseases through chronic antigenic stimulation. This study demonstrates that harboring HSP90-SUMO1 identifies healthy individuals at risk for plasma cell dyscrasias and that dominant inheritance of posttranslationally modified autoantigenic paratargs is one of the strongest molecular defined risk factors for MGUS, MM, and WM.